Sustainable marketing planning - Richardson, Neil (London Routledge, 2024)
This book provides practical insights, tools and frameworks to help readers produce tactically and strategically appropriate marketing plans. Showing how to embed sustainability in these strategies, students will be shown how to implement changes while being encouraged to reflect on why they are needed. The text reflects on contemporary themes that impact on Sustainable Marketing Planning, including consumer behaviour, entrepreneurialism, internal marketing, services, international marketing, event management and digital marketing. The 2nd Edition has been fully updated with a greater focus on the issues surrounding sustainability, including the environmental challenges facing businesses, sustainable accreditation and integrating the UN SDGs. It provides background on the value discourses that underpin sustainability, incorporates new examples and case studies from broader regions around the world, and introduces TBL-based loyalty. Full of tools and frameworks to improve comprehension, including chapter-by-chapter learning outcomes, summaries, exercises, applied activities and mini case studies, it bridges the gap between theory and practice effectively and accessibly. Presenting contemporary themes and challenges at the cutting edge of business research and practice, this book should be core reading for advanced undergraduate and postgraduate students of sustainable marketing, marketing planning and marketing strategy, as well as professionals seeking to improve the competitive advantage of their organisations.
Keywords: Green marketing; Consumption (Economics)--Environmental aspects; Social responsibility of business